THE CORRELATION BETWEEN BODY IMAGE AND COSMETIC CONSUMPTIVE BEHAVIOR IN NURSING STUDENTS AT PEKANBARU - Febtrina, Rizka; Anjani, Cici; 'Irfan, M. Zul; Kharisna, Dendy; Dyna, Fitri (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: The increasing use of cosmetic products opens up opportunities for female college students to buy cosmetics. Excessive purchases of beauty tools for female students due to dissatisfaction about their body shape, so female students tend to beautify themselves by buying products that can highlight physical shapes that are considered attractive. The purpose of this study is to analyze the correlation between body image and cosmetic consumptive behavior in nursing students in Pekanbaru. Method: This study is quantitative research with a cross-sectional design. This research was conducted at one of the nursing education institutions in Pekanbaru The sampling technique uses probability sampling technique with stratified random sampling type with a total of 219 respondents. Instruments used the MBSRQ-AS (Multidimensional Body Self Relation Questionnaire-Appearance Scales) questionnaire and the cosmetic consumptive behavior questionnaire. The statistical test used is chi-square. Results: The results of this study concluded body image was negative as many as 116 respondents (53%) and had consumptive behavior as many as 126 respondents (57.5%). Conclusions: That there was a significant correlation between body image and cosmetic consumptive behavior in nursing students at Pekanbaru with p value = 0.000.